2021
DOI: 10.1186/s12931-021-01776-y
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness of early intervention with fixed-dose tiotropium/olodaterol vs tiotropium in Japanese patients with COPD: a high-dimensional propensity score–matched cohort analysis

Abstract: Background Escalation to triple therapy (long-acting muscarinic antagonist/β2-agonist, inhaled corticosteroid [ICS]) in chronic obstructive pulmonary disorder (COPD) is recommended for patients on LAMA/LABA combinations with frequent exacerbations and severe symptoms. An extended time-to-escalation to triple therapy suggests patients are in a stable condition and is an indicator of treatment effectiveness. No studies in Japanese clinical practice have compared the effectiveness of LAMA/LABA fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
3
2
0
Order By: Relevance
“…Healthcare professionals rely on spirometry to confirm a diagnosis of COPD [ 29 ]; therefore, the timing of therapy initiation may be affected by the specialty of the treating physician. The rates of moderate or severe exacerbations among patients analyzed in our cohort were consistent with those described previously in the Japanese population [ 25 , 26 , 30 ]. The incidence of COPD exacerbations may be lower in Japan than in other countries because Japanese physicians often use asthma-COPD overlap as a disease label, resulting in an underreporting of the incidence of COPD exacerbations [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Healthcare professionals rely on spirometry to confirm a diagnosis of COPD [ 29 ]; therefore, the timing of therapy initiation may be affected by the specialty of the treating physician. The rates of moderate or severe exacerbations among patients analyzed in our cohort were consistent with those described previously in the Japanese population [ 25 , 26 , 30 ]. The incidence of COPD exacerbations may be lower in Japan than in other countries because Japanese physicians often use asthma-COPD overlap as a disease label, resulting in an underreporting of the incidence of COPD exacerbations [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…The baseline sociodemographic characteristics of the patients included in the present cohort were consistent with those in previous studies [ 25 , 26 ], although the prevalence of each comorbidity was lower than that described previously in the Japanese population [ 27 ]. Since the current database only includes registered facilities, information regarding comorbidities may not be available for patients if they were diagnosed or received treatment at non-registered facilities.…”
Section: Discussionsupporting
confidence: 89%
“…For example, a registry study by Tanabe et al [ 11 ] on patients with PH associated with respiratory disease had a population with a mean age of 67 ± 11 years and was 70% male. Other studies using data extracted from the MDV database in Japan on patients with idiopathic pulmonary fibrosis and COPD also estimated a high percentage of elderly patients and a predominantly male population which is in line with our study [ 22 , 28 ]. Our findings are consistent with studies using the COMPERA registry which involved elderly patients [ 6 , 29 , 30 ] as well as another recently published study using data from both the COMPERA and ASPIRE registries [ 30 ] which partially observed patients (patients with idiopathic pulmonary artery hypertension (IPAH) with a lung phenotype and patients with group 3 PH) with similar backgrounds to our study.…”
Section: Discussionsupporting
confidence: 90%
“…A Japanese real‐world study suggested that, compared with new users of tiotropium, new users of tiotropium/olodaterol had a numerically lower probability of escalating to triple therapy or experiencing moderate or severe COPD exacerbations 94 . Furthermore, data from the US HealthCore Integrated Research Database revealed that both individually and in combination, tiotropium/olodaterol was associated with a lower risk of COPD exacerbations, pneumonia and escalation to triple therapy in patients with COPD compared to ICS/LABA 95 ; the combined risk was reduced regardless of baseline eosinophils or exacerbation history.…”
Section: Efficacy Of Dual Bronchodilation In the Real Worldmentioning
confidence: 99%
“…93 A Japanese real-world study suggested that, compared with new users of tiotropium, new users of tiotropium/olodaterol had a numerically lower probability of escalating to triple therapy or experiencing moderate or severe COPD exacerbations. 94 Although initial optimisation of bronchodilation is not suggested in current COPD treatment guidelines or strategies, 1,4 in our opinion it is now appropriate to consider starting treatment with a LAMA/LABA combination as soon as the diagnosis of COPD is made. 96 The goal of pharmacological therapies in the treatment of patients with COPD is to reduce symptoms as well as improve health status and exercise tolerance, and reduce the risk of exacerbations.…”
Section: Efficacy Of Dual Bronchodilation In the Real Worldmentioning
confidence: 99%